P5 5 Nuclear Fusion: A Finite Resource? - Sanjeevvijay, Shaswathan; Munt, Leon; Iordanidis, George (Physics Special Topics, 2024)
The studies in this paper explore the limits of nuclear fusion, specifically looking at deuterium and tritium fusion, the primary fuels used in nuclear fusion reactors. The calculations within this paper find that on Earth, the abundance of lithium-6 is the limiting factor in this reaction and the ocean reserves would be able to fuel anthropogenic activities on Earth for 7.1 million years given the total energy usage on Earth from 2023.